(untitled) (Comparative & International Education Series, 2022)
Drawing on comparative research from two countries (Turkey and the United States), this chapter examines global engagement by doctoral students, the influence of this engagement on degree completion and employability, and how the consequences for higher education have been shaped by the ongoing COVID-19 pandemic and other events. Considerations are given to global university/industry linkages that determine student employability after degree completion; expected career trajectories specific to an individual country/context as an element of decision making; and expectations for faculty supervisors and institutions to support doctoral students during a time of global turmoil and uncertainty. Conclusions are offered as to ways in which employability and degree outcomes might be best understood in the context of globalization.